1996
DOI: 10.1038/bjc.1996.549
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of the matrix metalloproteinase inhibitor, batimastat, in a human colorectal cancer ascites model

Abstract: Summary The matrix metalloproteinase inhibitor batimastat was administered to a human colorectal cancer ascites model, which was initiated by injection of C170HM2 cells into the peritoneal cavity of SCID mice and resulted in solid tumour deposits and ascites formation. The cell line expressed both the 72 and 92 kDa forms of gelatinase by zymography. Batimastat administered from day 0 (40 mg kg-1) reduced the volume of ascites to 21 % of control in mice treated from day 0 (P <0.002) but not day 10. Formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…Subsequent autopsy studies demonstrated that the tumour was encapsulated in a dense fibrous stro ma with necrosis of some tumour cells [90]. Similar results have been reported in a human colorectal ascites xenograft model [91]. Batimastat was also shown to inhib it locorĂ©gional regrowth and mĂ©tastasĂ©s of a human breast carcinoma (MDA-MB-435) following resection in athym ie nude mice [92], Wang et al [93] orthotopically implanted fragments of human colonic carcinoma into athymie nude mice.…”
Section: Preclinical Studies Of Mmp Inhibitors In Cancersupporting
confidence: 64%
“…Subsequent autopsy studies demonstrated that the tumour was encapsulated in a dense fibrous stro ma with necrosis of some tumour cells [90]. Similar results have been reported in a human colorectal ascites xenograft model [91]. Batimastat was also shown to inhib it locorĂ©gional regrowth and mĂ©tastasĂ©s of a human breast carcinoma (MDA-MB-435) following resection in athym ie nude mice [92], Wang et al [93] orthotopically implanted fragments of human colonic carcinoma into athymie nude mice.…”
Section: Preclinical Studies Of Mmp Inhibitors In Cancersupporting
confidence: 64%
“…Watson et al [33] evaluated the effect of batimastat on a human colorectal cancer ascites model, which was initiated by injection of C170HM 2 cells into the peritoneal cavity of severe combined immunodeficient (SCID) mice. The inoculation of ascites cells resulted in solid tumor deposits and ascites formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their antitumor activity might be enhanced when used in combination with conventional chemotherapeutic agents. Despite impressive preclinical anticancer activity [28][29][30][31][32] and the suggestion of biological activity in phase I and phase II trials, 33,34 the MMPIs as a single agent or in combination with chemotherapeutic agent have been disappointing thus far in randomized clinical trials for solid tumors. 35,36 However, given the role of MMPIs in colorectal tumorigenesis, the synthetic MMPIs could find an even more important role in primary and/or secondary colorectal cancer prevention than in the treatment of established disease.…”
Section: Discussionmentioning
confidence: 99%